k-NEAREST NEIGHBOR AND LINEAR REGRESSION IN THE PREDICTION OF THE ARTIFICIAL FORM FACTOR - Souza, Deivison Venicio; Nievola, Júlio Cesar; Corte, Ana Paula Dalla; Sanquetta, Carlos Roberto (Floresta, 2020)
<p class="Paragraph SCXW29078370 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 37px; margin-right: 41px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k-nearest neighbor and linear regression in the prediction of the artificial form factor<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">. T<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">he proposal of this study<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">was to <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">test <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">whether<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> the performance of the non<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">parametric approach <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-Nearest<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">Neighbor (<span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-NN), <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">would improve estimates<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">of individual artificial form factor <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">(<span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">f<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">1.3<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">) <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">of<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">trees of the hybrid <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">Eucalyptus <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">urophylla<span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> x Eucalyptus <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">grandis<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">compared to the <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">O<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">rdinary <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">L<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">east <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">S<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">quares method.<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">A total of<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">149 sample-trees <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">were selected<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">, <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">felled<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">,<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">and <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">diameter <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">was <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">measured along the <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">trunk <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">at<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">10% (d<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">0.<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">1<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">), 30% (d<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">0.<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">3<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">), 50% (d<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">0.<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">5<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">) and 70% (d<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">0.<span class="TextRun SCXW29078370 BCX2" style="font-size: 7pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">7<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">)<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> of commercial height and posteriorly <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">at<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> 2m<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> intervals<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">. <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">Mathematical models recognized in the literature for<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> predicting the form factor were adjusted<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">for comparison<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">. The hyperparameter <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> of optimum adjust<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">ment<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> for the <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-NN estimator was obtained by repeated cross-validation. <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">The training data of the <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-NN regression model were identical to those used in the adjustment of the linear regression models<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> since m<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">ost multiple linear regression models present problems of collinearity or multicollinearity. The use of the covaria<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">te(d0.3.d0.7)/d1.32<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> and <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> = 15 made it possible to construct <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-NN models with better generalization capacity. The potential of the <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-NN estimator to predict the artificial form factor and thus to obtain less biased estimates of individual tree volumes was <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">demonstrated<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">and considered <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">to be <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">superior to the use of linear regression and average form factors. <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">The <span class="TextRun SCXW29078370 BCX2" style="font-style: italic; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">k<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">-NN approach can be considered more generic<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">for<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">predicti<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">on of<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> the tree form factor<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">,<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">and its use<span class="TextRun SCXW29078370 BCX2" style="color: #000000; font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="none">is<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto"> recommended when classical linear regression models or other simpler methods do not <span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">yield<span class="TextRun SCXW29078370 BCX2" style="font-size: 9pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 14px;" lang="EN-US" data-contrast="auto">good results.<span class="EOP SCXW29078370 BCX2" style="font-size: 9pt; line-height: 14px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props=""201341983":0,"335551550":6,"335551620":6,"335559685":567,"335559737":617,"335559739":160,"335559740":240">